The magnetic properties of Mn5Ge3 thin films grown on PMN-PT - Ozdemir, O.; Mikailzade, F.; Arslan, L. Colakerol (Elsevier, 2022)
The authors report the thickness dependent structural and magnetic properties of Mn5Ge3 thin films with different Mn layer thicknesses in the range from 5 nm to 30 nm deposited on Pb(Mg1/3Nb2/3)(0.7)Ti0.3O3 (PMN-PT) substrates using solid phase epitaxy. Gradual decrease of the surface roughness due to the formation of larger grains, as well as the decrease of the coercivity and squareness ratio on increasing of Mn layer thickness has been observed. It has been revealed that the slightly greater value of the saturation magnetization than the corresponding one observed early for thin films and bulk samples is associated with the presence of structural defects. The ferromagnetic resonance (FMR) spectra have been obtained to be isotropic for the films with 5 nm thickness, whereas those registered from the films with the thicknesses of 10 nm and above demonstrated in-plane magnetic anisotropy, which have been interpreted as to be resulted from magnetocrystalline anisotropy as well as the stress-induced magnetic anisotropy. These results are suggested to create a major interest in the development of magnetoelectric heterostructured devices based on strain coupling that are compatible with CMOS technology.
Keywords: Mn5ge3 Thin-Films; Temperature; Roughness; Mn